A New Politics of Identity - PAREKH, Bhikhu (Palgrave, 2008)
The New Politics of Identity pursues many of the central issues raised in the author's Rethinking Multiculturalism focusing in particular on their consequences for global politics. Parekh develops a theory of identity that combines respect for diversity and applies this theory to a range of key current debates on national identity.